Pólya’s influence on (my) research - Rott, Benjamin (Teaching Mathematics and Computer Science, 2022)
In this article, I outline the influence of George Pólya's work on research in different areas and especially on mathematics education, namely heuristics and models of the problem-solving process. On a more personal note, I will go into some details regarding Pólya's influence on my own work in mathematical problem solving with a focus on the research project for my PhD thesis.Subject Classification: 97xxx